Effectiveness of the 10-valent pneumococcal conjugate vaccine among girls, boys, preterm and low-birth-weight infants – Results from a randomized, double-blind vaccine trial. Issue 28 (19th June 2019) - Nieminen, H.; Rinta-Kokko, H.; Jokinen, J.; Puumalainen, T.; Moreira, M.; Borys, D.; Schuerman, L.; Palmu, A.A.
Highlights: Pneumonia and otitis were more common among boys than girls. Pneumonia incidences were higher among premature infants than among term infants. PHiD-CV10 had a similar effectiveness in both sexes. VE point estimates of PHiD-CV10 at same level among preterm and term infants. Abstract: Background: Several studies have shown differences in susceptibility to infections and immune response to vaccines by sex. Prematurely born infants are at higher risk for pneumococcal diseases, with lower effectiveness for some vaccines compared to term infants. We have reported the effectiveness of the 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10) on several endpoints in the Finnish Invasive Pneumococcal disease (FinIP) vaccine trial. Now, we present the results of a post-hoc analysis evaluating PHiD-CV10 effectiveness in subgroups by sex, gestational age, and birth weight. Methods: The FinIP trial was a phase III/IV cluster-randomized, double-blind trial. Infants enrolled < 7 months of age received PHiD-CV10 in two thirds of clusters (3 + 1 or 2 + 1 schedule) and hepatitis B vaccine as control in remaining third. Outcome data included invasive pneumococcal disease, pneumonia, tympanostomy tube placements, and antimicrobial purchases collected through national, routinely used health registers. Negative binomial model was used in the incidence and vaccine effectiveness estimation, and differences in incidences between subgroups were tested among control children. Results: Of the 30, 527 infants enrolled 51% were boys. The incidences of hospital-diagnosed pneumonia and otitis-related outcomes were higher among boys in control groups. There were no significant sex differences in the vaccine effectiveness estimates. Altogether, 1519 (5%) infants were born before 37th gestational week. The incidences of pneumonia outcomes were higher among premature infants when compared to term infants. The vaccine effectiveness estimates among preterm infants were not statistically significant except for antimicrobial purchases, but all point estimates were at the same level among preterm infants as among term infants. There was no significant difference between 2 + 1 and 3 + 1 schedules in any of the subgroups analysed. Conclusion: PHiD-CV10 had a similar effectiveness in both sexes, and seemed to be protective in preterm infants. Trial registration:ClinicalTrials.gov NCT00861380 and NCT00839254